(untitled) (Bangladesh Journal of Public Administration, 2021)
Working parents in Bangladesh are facing tremendous challenges to be self-dependent both socially and economically in addition to raise and to educate their children in a sound and secure way. Regarding the issue, caring for the children has been appeared as a vital social demand due to the increasing number of working parent’s attachments to a variety of economic and social activities which displays timely Day Care service requirements. To find out the present condition of the daycare centres in Bangladesh and to know the impact of daycare centres on working parents in Dhaka city, a research has been carried out in Dhaka city based on qualitative data. In this rigorous process, data has been gathered from 30 respondents, which includes working parents who have babies, experts, owners of Day Care service centre, and staff. The study found that almost all the respondents are satisfied with the services are providing by the private sector’s daycare centres and the working parents who keep their babies in Daycare service centre, they can continue their work and job unworriedly by keeping their babies in Day Care Centres. Both father and mother are contributing to their family, their standard of living is increasing, and economically working parents are getting solvent. Findings revealed that the enhancement of working parents creates the demand of healthy daycare centres exponentially. The endorsement has been made to augment the services provided by these daycare centres with the aid of proper amenities. Lastly, these types of services can play a significant role in promoting a suitable, healthy, and secure childhood environment for our children, and even it can be the essential stakeholder of Sustainable Development if it is flourished and patronized properly.